Axial expansion for prompt safety of a small lead-cooled reactor. (November 2020) - Zhang, You-Peng; Wallenius, Janne; Gu, Long; Yang, Sheng; Zhao, Yi-Yang; Li, Jin-Yang; Peng, Tian-Ji
Highlights: Axial expansion effects on core safety was investigated for U-free fuel cases. Oxide and metallic fuel cases provide different safety related coefificients. Axial expansion of fuel can provides sufficient prompt negative feedbacks. Abstract: We have investigated axial expansion as means of achieving core safety during unprotected transients in Pb-cooled fast reactors with minor actinide driver fuel. Adopting identical linear rating and fuel rod/assembly geometry, it is shown that axial expansion of the fuel provides sufficient prompt negative feedback to avoid fuel damage if a fast reactivity insertion is limited to 40 pcm for aoxide fuel and 100 pcm for a metallic alloy fuel.